200 Years of Belgian Horn School? A Comprehensive Study of the Horn in Belgium, 1789-1960 - Billiet, Jeroen (Ghent Orpheus Instituut, 2008)
Horn player Jeroen Billiet intensively researched, under the lead of the Orpheus Institute, and tutor Claude Maury, the origin, development, use, playing style, instrumental manifacture, repertoire and people behind the tradition of hornplaying present in the Belgian region.A report of this 7-year long study is to be read in the (English-written) dissertation: 200 years of Belgian Horn School? A Comprehensve Study on the Horn in Belgium, 1789-1960.
Dissertation for the Approval of a Laureate Programme at the ORCiM-Orpheus Research Center in Music, Ghent, 2008